IMPLEMENTASI METODE ADDIE DALAM PENGEMBANGAN APLIKASI VIRTUAL TOUR KAMPUS BERBASIS WEB PADA POLITEKNIK NEGERI SAMBAS - Noferianto Sitompul; Vanie Wijaya; U Heri Mulyanto (LPPM Universitas Abdurrab, 2025)
As one of the state universities located in the province of West Kalimantan and directly adjacent to neighboring Malaysia, Sambas State Polytechnic strives to increase the enthusiasm of the young generation in continuing their education to the tertiary level, by trying to increase the number of students through socialization regarding information about the Sambas State Polytechnic campus to prospective SLTA/MA graduates in various districts/cities in West Kalimantan Province. Sambas State Polytechnic itself is a vocational college that has 10 study programs, which presents its campus information by delivering the profile of Sambas State Polytechnic through the campus website media, Facebook and Instagram social media, and using PowerPoint slides. The results of interviews with the Poltesa socialization public relations found that the weakness was that the public did not fully understand the information presented, as evidenced by several prospective students still choosing campuses outside Sambas Regency. For this reason, a new socialization media innovation is needed to display the entire campus environment virtually as a virtual tour. This virtual tour will depict the real conditions of the campus, starting from the campus entrance, and learning support facilities, to study program rooms such as laboratories and workshops, which can be accessed online on the web, either via gadgets or computers. Virtual Tour technology allows users to explore the real environment virtually. The development of this web-based virtual tour application is a continuation of previous research and implementation of a new method, namely the ADDIE development method where the stages start from the Analysis, Design, Development, Implementation, and finally Evaluation stages. This method was chosen because the development method allows each phase to be evaluated and revised from the stages passed so that the resulting product is of higher quality. This web-based virtual tour application is expected to provide benefits, namely providing convenience for visitors and prospective students to get to know the Sambas State Polytechnic campus. From the results of the material expert test, 89.2% and the general public 86.83%, the Sambas State Polytechnic virtual tour website is very suitable for use as a digital information media, so in 2025 it is hoped that there will be an increase in prospective student interest of 5%.